An Attempt to Train Nurses at the General Hospital in Prague in the Fourth Decade of 19th Century - Hlaváčková, Ludmila (Theatrum historiae, 2013)
The professional education of nursing staff in Bohemia started initially at the convents of the order of Merciful Brethren. The first case was documented in 1745 in the city of Valtice. However, most of the nursing staff remained without formal education. The nursing personnel at the Prague General Hospital, which was founded in 1790/91, did not have an opportunity to undergo a professional training long into the 19th century. This paper describes the first attempt to introduce a formal professional schooling of the nursing staff in the General Hospital in Prague. The idea was proposed by prof. assoc. J. G. Riedel at the beginning of 1845. Nevertheless this initial plan was not put into practice probably as result of financial difficulties.